The Persuasive Agency of Objects and Practices in Alfred the Great’s Reform Program - Pitt, Georgina (Arc Humanities Press, 2024)
Alfred the Great's early English kingdom was the only one to resist Viking conquest. His reform program strengthened the kingdom and enabled it to hold fast against the Vikings. But texts are largely silent on the process of reform. There has been a tendency to assume that these reforms would obviously be beneficial, but Alfred’s elites were not to know that in advance. What motivated them to do as their king bid them?